KEWENANGAN BADAN PEMERIKSA KEUANGAN DALAM MELAKUKAN PEMERIKSAAN DANA DESA YANG BERSUMBER DARI APBN - Mutawalli, Muhammad (Faculty of Law, Universitas Pasundan, 2022)
This research was conducted in order to understand and be able to describe the form of authority of the Audit Board of Indonesia under Law No. 15, 2006 concerning the Audit Board of Indonesia regarding the audit of village funds sourced from the state budget in village administration reviewed from the state administration system in Indonesia. The discussion in this writing is about what is the standing of the Audit Board of Indonesia in auditing the village fund in the village administration and the authority of the board in auditing the fund at the village administration. This research used normative approach through scientific study and aimed to ensure the concrete and conformity of the board authority normatively. The research was conducted through library research by studying and analyzing written legal materials and supported with the statements of informant and correspondent involved. The findings concluded that the Audit Board of Indonesia as the state organ of Indonesia with vital task to audit the state budget that can be considered as the Supreme Audit Institute either in the level of central government or the regional level. The authority of the board in the level of village administration to audit the village fund that comes from the state budget is a political movement of the government and is considered as the state will in realizing the good governance as the state program. However, in the implementation, the Audit Board of Indonesia has established its representatives in each province of Indonesia in which, unfortunately, the regional representative seemed meaningless since the board representatives have to answer to the Head and Deputy Head of the board regarding the examination and audit of the village fund of the state budget. The author suggests to promulgate additional concrete and clear provisions on the duty of the representatives of the board in every province. Keyword: BPK (the Audit Board of Indonesia) Village Fund, Village Administration.